3D‐Printed Triboelectric Nanogenerators: State of the Art, Applications, and Challenges. Issue 3 (8th February 2021) - Mahmud, M. A. Parvez; Zolfagharian, Ali; Gharaie, Saleh; Kaynak, Akif; Farjana, Shahjadi Hisan; Ellis, Amanda V.; Chen, Jun; Kouzani, Abbas Z.
Abstract : Triboelectric nanogenerator (TENG) development is undergoing rapid progress utilizing the state‐of‐the‐art 3D‐printing technologies. Herein a critical analysis of the latest developments in 3D‐printed wearable and implantable TENGs that can be used to energize small portable electronic and biomedical devices is presented. Recent progress in 3D‐printed triboelectric nanogenerator (3DP‐TENG) materials and architectural formations, as well as their performance, is evaluated for powering systems that implement physiological monitoring, multifunctional sensing, electronic energizing, noise canceling, dust filtering, and self‐healing. Furthermore, the review explicitly focuses on the 3D‐printing approaches used to form stable and robust 3DP‐TENGs. In addition, the key challenges to improving the performance of 3DP‐TENGs for optimal energy harvesting are discussed, and a roadmap is given for research and translation to commercial markets in the next decade. Abstract : Herein the recent developments in triboelectric nanogenerators (TENGs) fabricated using 3D‐printing technologies are highlighted. Material functionalization, device structure formation, optimal energy harvesting, system integration, and translation to commercial market are covered. The approaches needed to overcome the current challenges to developing 3D‐printed TENGs and integrating them into host systems are discussed.